Plotting a Path Forward: Towards a Supportive Graduate Writing Program - Keith O'Regan (Canadian Journal for the Scholarship of Teaching and Learning)
Writing centres in Canada have an important role to play in aiding dissertation writers in the planning and composing of doctoral work. While doctoral writing support may challenge the conventional offerings that are currently provided in more traditional undergraduate writing centre environments, there is nevertheless a demonstrable need for this form of support. This article reviews the effectiveness of a writing support program with an attention to questions of genre, metadiscursive awareness, disciplinary conventions, and the program’s capacity to assist dissertation writers with completing large sections of work through building feelings of self-belief and self-advocacy. By analyzing survey results, the author argues that a focus on writing process and reflection at the PhD level can be instrumental in building momentum towards completion through overcoming social isolation, by increasing students’ agency and ownership over the project, and in building graduate-level writerly confidence.